Racial/ethnic differences in associations between neighborhood socioeconomic status, distress, and smoking among U.S. adults. Issue 1 (2nd January 2016) - Karriker-Jaffe, Katherine J.; Liu, Huiguo; Johnson, Renee M.
ABSTRACT: Neighborhood disadvantage may increase smoking by increasing distress, while neighborhood affluence may reduce smoking by increasing positive affect. We examined whether relationships between neighborhood socioeconomic status (SES) and daily smoking operated through distress and positive affect. Simultaneous multivariate path models used pooled cross-sectional data from the 2000 and 2005 National Alcohol Surveys (15, 963 respondents; weighted N  = 10, 753) and the 2000 Decennial Census. Multiple groups analysis assessed differences by gender and race/ethnicity. Covariates included neighborhood immigrant concentration and individual-level demographics. In the full sample, neighborhood disadvantage significantly increased smoking and neighborhood affluence significantly decreased smoking, with no indirect paths through either distress or positive affect. Unique among Hispanics, affluence resulted in decreased smoking indirectly through reduced distress. Relationships between affect and smoking also varied by race/ethnicity, with no significant differences by gender. Interventions targeting neighborhood socioeconomic status and distress may help reduce smoking, particularly for racial/ethnic minorities.